Extravascular foci of Trypanosoma vivax in goats. The central nervous system and aqueous humor of the eye as potential sources of relapse infections after chemotherapy - Whitelaw, D.D.; Gardiner, Peter R.; Murray, M. (Cambridge University Press, 1988)
Relapse of parasitaemia after drug treatment of trypanosome infections is normally attributed to drug-resistance on the part of the parasite, under-dosage of the drug or reinfection of the host. In addition, inaccessibility of parasites to drug through sequestration in privileged extravascular sites has been shown in the past to occur withTrypanosoma brucei, and we have obtained evidence that extravascular foci ofT. vivaxcan also serve as a source of relapsing infections. Infection of goats with a West African stock ofT. vivaxresulted in severe illness, which was fatal if untreated. During the terminal stage of an acute infection, clinical signs of central nervous system involvement were apparent. Histologically, the choroid plexus was swollen and oedematous, and in some cases meningitis or meningoencephalitis was seen. Trypanosomes could be detected in the cerebrospinal fluid, and also extravascularly in the choroid plexus and meninges. In three cases they were present in the aqueous humor, associated with corneal cloudiness or opacity. Treatment of 2 goats with the trypanocidal drug diminazene aceturate eliminated parasitaemia, but infections in both relapsed about 6 weeks later, despite trypanosomes being undetectable in the bloodstream during the intervening period. We conclude that the relapse infections were caused by re-emergence of trypanosomes from the CNS and/or the eye, where sequestered parasites may have been inaccessible to the trypanocide.